Keberadaan Tanah Absentee kini (Studi kasus di Kota Parepare, Sulawesi Selatan) - Auliah Ambarwati; Sri Meliana; Phireri Phireri; Muhammad Darwis (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This study aims to determine the application of Law No. 5 of 1960 concerning agrarian matters to land owned by an absentee and to find out the legal consequences that arise on absentee land ownership. This research uses normative legal research with a statute approach. Types and sources of legal materials using primary legal materials and secondary legal materials. Data analysis was studied descriptively. The results showed that there was no form of law enforcement carried out by the Parepare City Land Office. This is because when the land has been registered and the certificate has been issued, the authority to use the land becomes the full authority of the land owner. The Land Office has never carried out supervision or reprimand for land owners who abandoned their land without being used to obtain results. The Land Office only makes a statement in each certificate issuance process which is then signed by the applicant. If the applicant violates these provisions, the Land Office only hands off and submits it entirely to the land owner.